MAKSIMALISASI POTENSI ZAKAT MELALUI PENINGKATAN KESADARAN MASYARAKAT - SITI NURHASANAH; SURYANI SURYANI (Universitas Islam Negeri Imam Bonjol Padang, 2018)
The theme of the article is: zakat management. The purpose of the article is: to examine the potential of zakat to overcome poverty. The research method used in this research is qualitative research methods. Zakat is a property that must be issued by a Muslim to give to those who have the right to receive it in accordance with Islamic law. The analysis shows that zakat can reduce the number of poor families from 84% to 74%. This shows the extraordinary potential of zakat which can prosper the people. Therefore the people need to be made aware of the importance of fulfilling the obligation of zakat. This awareness can be through socialization and education to the public related to the law, the wisdom of zakat, the assets of the zakat object as well as the procedures for calculation, and the relation between zakat and taxes. This is the duty of the government and the community to continue to campaign for zakat.